Optimizing antibiotic therapy of group IV community-acquired pneumonia patients - Dziublyk Ya.O. (Medičnì Perspektivi)
The aim of the study was to evaluate the clinical and economical effectiveness of differentiated antibacterial therapy of group IV patients with community-acquired pneumonia (CAP). Materials and methods. 42 patients, admitted to the hospital with severe CAP without risk factors for P. aeruginosa infection were randomized in three groups in 1:1:1 ratio. All patients received sequential antibacterial therapy with i.v. amoxicillin/clavulanate or ceftriaxone, or ertapenem in combination with azithromycin switched to oral amoxicillin/clavulanate, cefuroxime axetil in combination with oral azithromycin or levofloxacin, respectively, after initial improvement in 3–4 days. A comparative effectiveness analysis was performed based on clinical, laboratory and economic data. Results. Treatment outcomes in all subgroups of patients were similar: in 1st subgroup the cure rate was (28,6  12,1) %, improvement – in (49,4  13,2) % of patients; in 2nd and 3rd subgroups the cure/improvement rates were (35,7  12,8) and (42,9 13,2) %, respectively (р  0,05). Conclusion. Antibacterial therapy, always empiric and differentiated depending on severity of disease, con¬comitant conditions and previous use of antibiotics within 3 months of the onset of the disease, is a milestone of treatmet of CAP patients. A sequential antibiotic therapy with either aminopenicillin (amoxicillin/clavulanate) of 3rd generation cephalosporin (ceftriaxone/cefuroxime axetil) in combination with macrolide (azithromycin) or carbapenem (ertapenem, followed by levofloxacin) is recommended in hospitalized clinical group IV CAP patients without risk factors for P. aeruginosa infection. In current group of patients pharmacoeconomic analysis confirmed the expediency of administration a sequential antibiotic therapy with parenteral amoxicillin/clavulanat or ceftriaxone in combination with azithromycin, followed by oral amoxicillin/clavulanat or cefuroxime axetil in combination with azithromycin upon stabilization of patient’s condition.